Export Position of Indonesian Mango Commodities in the International Market (Case Study in Seven Destination Countries) - Chory Aura; Sri Widayanti; Nisa Hafi Idhoh Fitriana (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Indonesian mangoes have an excellent opportunity to participate in the international market, but amid intense competition in the international market, Indonesian mangoes feel unable to compete. This study analyzes trade specialization, comparative advantage, and competitive advantage, as well as Indonesia's position as a mango exporter in the global market. The Trade Specialty Index (TSI) is a method used to analyze trade specialization, while Revealed Comparative Advantage (RCA) is a method for analyzing comparative advantage, and Export Product Dynamics (EPD) is a method for analyzing competitive advantage and market position for Indonesian mangoes. The study falls under the quantitative category because it uses secondary data in the form of a time series that spans ten years, from 2012 to 2021. The research uses India, Thailand, and Pakistan as comparison countries and Singapore, Malaysia, France, the Netherlands, the United Kingdom, Spain, and Germany as destination countries. According to the results of the TSI analysis, Indonesian mangoes exhibit trade specialization as importers in five destination countries, except for Malaysia and Singapore. Malaysia and Singapore are in the growth stage, Germany is in the introduction stage, and four other countries are in the import substitution stage. According to the average value of revealed comparative advantage (RCA), only two of the seven destination nations, Malaysia and France, exhibited strong competitiveness for Indonesian mangoes. The Export Product Dynamic (EPD) matrix reveals that Indonesian mangoes are in a retreating position toward the markets of Malaysia and Singapore. At the same time, the other five target countries are in a falling star position. Increasing the value of TSI, RCA, and EPD can be accomplished by improving post-harvest technology to increase production quantity and quality and developing marketing networks.